Animal Subjectivity and Child Animality in Children’s Media: Review of Amy Ratelle, Animality and Children’s Literature and Film - Monteleone, Amanda (Humanimalia, 2020)
Amy Ratelle, Animality and Children’s Literature and Film. New York: Palgrave Macmillan. 2015. viii + 171 pp. $93.48 (hc); $79.99 (e-book).